Factors affecting purchasing behaviors of generic drugs versus originator counterparts in Jordan - Maha N. Abu Hajleh, Ali AL-Samydai, Zahraa Aloosi, Raghad Abuhamdan, Sumaiah Al.Naimat, Lina Abdelfattah, Lidia Al-Halaseh (Journal of Applied Pharmaceutical Science, 2021)
Background: The use of generic drugs is increasing in several countries due to their lower price while maintaining the same efficacy as their originator counterparts. But some concerns arise from the lack of knowledge or misunderstanding of the concept of bioequivalence and/or from manufacturers’ marketing efforts that lead consumers to switch back to branded drugs.Method: A random sample of 350 percipients has been enrolled; 304 had completed the questionnaire that was used in this study (regarding the factors influencing consumers’ preferences for generic vs. branded drugs). The forms have been distributed online (using Google Form) among all participants.Results: Results revealed that the most influential factor for participants when purchasing drugs was the role of the pharmacist. Lack of knowledge about the efficacy of drugs has the lowest effect on choosing the medication. Also, the price and confidence in brand-name drugs showed a statistically significant effect on selecting the medications.Conclusion: Generic drugs seem to be the best option for patients but a progressive alteration is required in people’s mentality to accept this fact. This can be done through promoting educational interferences to increase consumer and health system confidence in the capability of generic medications to treat chronic diseases.
Keywords: Bioequivalence, generic drugs, originator counterparts, economic benefits, purchasing/prescription behaviors.